Efek Latihan dengan Teknik Close Kinetic Chain terhadap Peningkatan Lingkup Gerak Sendi Lutut dan Kemampuan Fungsional Lutut pada Pasien Pasca Rekonstruksi ACL (ACLR): A Case Report - Handayani, Tri Mukti; Pristianto, Arif; Mardianto, Halim (Universitas Muhammadiyah Surakarta, 2024)
Introduction: ACL (Anterior Cruciate Ligament) is a ligament that helps stabilize the knee joint. This ligament is most frequently injured, usually occurring in football, basketball and other sports players. ACL injuries occur with high frequency in the United States, while in Indonesia, ACL injuries are the second most common case. ACL reconstruction (ACLR) is recommended and proven to be a very effective technique and usually provides satisfactory results. However, several complications will arise after undergoing ACLR in various ways, such as social status and function, functional ability, and the patient's quality of life, so a rehabilitation process is needed. Case Presentation: The article is a case report study with a teenage male patient in RSD K.R.M.T Wongsonegoro Semarang (brother D, 16 years old; height: 167 cm; weight: 50 kg; BMI: 17.9; occupation: student; hobby: football) post ACLR autograft hamstring 2 months ago on the left side of the knee. Patients entering the 2nd phase of rehabilitation are currently being given close kinetic chain exercises to increase the range of motion of the knee joint and the functional ability of the knee which will be evaluated using a goniometer and International Knee Documentation Committee (IKDC) evaluation form. Management and Outcome: Exercises using the Close kinetic chain technique can increase the range of motion of the knee joint and improve the functional ability of the patient's knee. Exercises are given after ACL reconstruction during phase 2 rehabilitation. Discussion: Training is carried out 3 times a week with training sessions lasting approximately 2 hours. The exercises given are static bike, squatting exercises, andclose kinetic chain exercise in the form of squats, lunges, single leg stance, and wall slides. Exercise can increase muscle strength, stability and muscle flexibility so that it can increase the range of motion of the joint in knee flexion movements and the functional ability of the knee. Conclusion: Special exercise programs provided by physiotherapy have an important role in the rehabilitation process. Static bike training, squat training, etcclose kinetic chain exercise in the form of squats, lunges, single leg stance, and wall slides are given to overcome condition problems after ACLR, especially in phase 2.